2014
DOI: 10.1093/ntr/ntu154
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-Pharmacodynamic Modeling of the Effect of Varenicline on Nicotine Craving in Adult Smokers

Abstract: Introduction: Varenicline has been shown to significantly reduce craving and several aspects of smoking reinforcement in clinical trials, compared with placebo. This is the first report describing the concentration-effect relationship of varenicline on relief of craving. Methods: The pharmacokinetics (PK) and pharmacodynamics (PD) of a single 2 mg dose of varenicline were investigated in 40 smokers in a randomized, crossover study comparing the effect of varenicline with placebo on ameliorating abstinence-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…Similarly, levels greater than 5 ng/ml plasma varenicline were associated with reduced rates of heavy drinking, though only 8 participants achieved plasma varenicline levels of ≥ 5. This is consistent with findings indicating that 2 mg/day varenicline decreased nicotine craving in smokers, and that this response was related to increased plasma varenicline levels (Ravva et al, 2015), although the pharmacokinetic data were also highly variable in that study. Together, our exploratory findings suggest that plasma varenicline levels may need to be greater than 5 ng/ml to be efficacious in reducing consumption in heavy drinkers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, levels greater than 5 ng/ml plasma varenicline were associated with reduced rates of heavy drinking, though only 8 participants achieved plasma varenicline levels of ≥ 5. This is consistent with findings indicating that 2 mg/day varenicline decreased nicotine craving in smokers, and that this response was related to increased plasma varenicline levels (Ravva et al, 2015), although the pharmacokinetic data were also highly variable in that study. Together, our exploratory findings suggest that plasma varenicline levels may need to be greater than 5 ng/ml to be efficacious in reducing consumption in heavy drinkers.…”
Section: Discussionsupporting
confidence: 91%
“…However, few studies have examined the relationship between plasma varenicline levels and drug-related outcomes. In a recent investigation on pharmacokinetic modeling of varenicline on nicotine craving, 2 mg/day varenicline decreased craving and the magnitude of this response was related to higher plasma varenicline levels in smokers, though this response was highly variable (Ravva et al, 2015). To date, there are no studies examining the relationship between plasma varenicline levels and drinking behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was first put forth by Reid and colleagues (2007) who conducted a laboratory study of topiramate's effects during a period of brief smoking abstinence and found that the medication had no effect on cue-induced craving and actually enhanced withdrawal. In contrast, each of the first-line smoking cessation aids has been found to have anticraving effects (Kotlyar et al, 2011; Ravva et al, 2015; Shiffman, 2008) with bupropion and varenicline also mitigating withdrawal-related negative affect (Cinciripini et al, 2013; Foulds et al, 2013). …”
Section: Discussionmentioning
confidence: 98%
“…Various clinical trials have demonstrated the effi cacy and safety of VCL in adults who initiate a smoking cessation program. A PK-PD analysis described a model for VCL that included using a two-compartment PK model with a linear PD model with fi rstorder onset/offset rate constants [ 17 ]. Craving reduction scores were associated with VCL plasma concentrations with a rapid onset under 1 h peaking at 3 h and were maintained for the next 4 h (the maximum time period studied).…”
Section: Varenicline (Vcl)mentioning
confidence: 99%